TEACHERS’ PROFESSIONALISM EFFECTIVENESS AT VHS IN EAST BEKASI - Tyas, E. Handayani (International Journal of Research -GRANTHAALAYAH, 2019)
This study is focused on the teachers’ professionalism effectiveness, it was done to find out how the teachers’ professionalism effectiveness at Vocational High School in East Bekasi. This study was conducted at East Bekasi in some private schools. The method of the study was qualitative with a descriptive design. The subjects of the research were the school headmasters, vice school headmasters, teachers, and Teacher Organization (TO). The instruments of this study are observation sheet and interview guidance. The data of the study were analyzed descriptively through the process of data reduction, data display, and concluding. The result of the study shows that the teachers’ ability improvement programs were done based on the teachers’ need every year, the teachers’ ability improvement program was done in and out of the school, there are some obstacles which are faced by schools in improving the teachers’ professionalism. So, it is concluded that the teachers’ professionalism program needs improving, and it should be goal-oriented. Besides, the obstacles which are faced by the school should be well overcome.